Identificación y evaluación de lo niveles de contaminación ambiental en la central hidroeléctrica de maria jiray que influyen en el deterioro del medio ambiente en el año 2005 - Inostroza Aguilar, Oswaldo Ricardo (2016)
This research has the overall objective to determine the levels of environmental pollution in the hydroelectric plant of Mary Jiray influencing the deterioration of the environment in 2005, and has been conducted to identify and assess the various environmental impacts that are generated in hydroelectric power projects that affect environmental degradation and thus issuing policies to reduce and eliminate pollution generated in the production of electricity from water resources. For this research monitoring of liquid effluents were made both in the loading chamber and the discharge channel. Likewise also they took place monitoring of noise generation sources (within the engine room) and environmental noise monitoring (outside the engine room) all within the hydroelectric plant. By making the identification and evaluation of environmental impacts generated by a hydroelectric generation, it was concluded that these are minimal and that are below the maximum allowable limits set by rules, except for the noise generated by sound sources this power plant and enter fluctuating 89.8 dB (A) and 98.7 dB (A), exceeding 100% of the measurements set as maximum allowable working environments for electrical measuring 80 dB (A) established by Regulation Occupational Health and Safety Electrical Sub Sector: RM No. 263-2001-EM / VME. Also 66.67% of ambient noise levels exceeded 80 dB (A) for noise nuisance; of these, 33.34% was above the reference allowable limit for harmful noise is 90 dB (A). Both established by Municipal Ordinance No. 015 of the Municipality of Lima. Note that this power plant is located far from population centers and environmental noise measurements were carried out as close to the outer walls.